2007
DOI: 10.1007/s10461-007-9318-4
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Medication Regimens: A Test of a Psychosocial Model

Abstract: Objective-The primary aim of this study was to test a psychosocial model of medication adherence among people taking antiretroviral medications. This model was based primarily on social cognitive theory and included personal (self-efficacy, outcome expectancy, stigma, depression, and spirituality), social (social support, difficult life circumstances), and provider (patient satisfaction and decision-making) variables. © Springer Science+Business Media, LLC 2007Correspondence to: Colleen DiIorio, cdiiori@sph.em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 47 publications
8
81
1
4
Order By: Relevance
“…Al respecto, una condición básica para este éxito terapéutico, compartida por muy pocas otras enfermedades, es un cumplimiento extremo de la indicación medicamentosa (adherencia). Pequeños incumplimientos de esta adherencia, se asocian a fracaso terapéutico (pérdida de la capacidad de suprimir la replicación viral con la consiguiente progresión de la enfermedad), agravado por la pérdida de efectividad de los anti-retrovirales previamente usados (desarrollo de resistencia) 29,[34][35][36] . Entre los factores psico-sociales más importantes para la pérdida de adherencia están: la falta de una red de apoyo social, el abuso de sustancias y la depresión 23,28,29,[34][35][36][37][38][39] .…”
Section: Factores Asociadosunclassified
See 1 more Smart Citation
“…Al respecto, una condición básica para este éxito terapéutico, compartida por muy pocas otras enfermedades, es un cumplimiento extremo de la indicación medicamentosa (adherencia). Pequeños incumplimientos de esta adherencia, se asocian a fracaso terapéutico (pérdida de la capacidad de suprimir la replicación viral con la consiguiente progresión de la enfermedad), agravado por la pérdida de efectividad de los anti-retrovirales previamente usados (desarrollo de resistencia) 29,[34][35][36] . Entre los factores psico-sociales más importantes para la pérdida de adherencia están: la falta de una red de apoyo social, el abuso de sustancias y la depresión 23,28,29,[34][35][36][37][38][39] .…”
Section: Factores Asociadosunclassified
“…Pequeños incumplimientos de esta adherencia, se asocian a fracaso terapéutico (pérdida de la capacidad de suprimir la replicación viral con la consiguiente progresión de la enfermedad), agravado por la pérdida de efectividad de los anti-retrovirales previamente usados (desarrollo de resistencia) 29,[34][35][36] . Entre los factores psico-sociales más importantes para la pérdida de adherencia están: la falta de una red de apoyo social, el abuso de sustancias y la depresión 23,28,29,[34][35][36][37][38][39] . Se considera que la depresión no tratada es, a su vez, un factor de riesgo para el abuso de sustancias y el uso de terapias alternativas o la automedicación, con el subsecuente perjuicio en la adherencia y efectividad de la TAR 4,11,18,28,31,32 .…”
Section: Factores Asociadosunclassified
“…Similarly, Trevino et al in a cross-sectional longitudinal study in Cincinnati, USA, reported that positive religious coping was associated with positive outcomes such as better QoL, improved clinical outcome, and adherence [47]. This findings in this study may have been due to the possible role of positive religious coping in helping patients maintain a positive attitude to life, promote active coping with health problems, fostering emotional wellbeing, establishing and maintaining social support, facilitating meaning making, and improved self-efficacy [48]. This is in tune with other studies in diverse settings, which reported positive association between the level of positive spiritual coping and the physical as well as mental health [4,49,50].…”
Section: Discussionmentioning
confidence: 53%
“…The positive association between social support and adherence to ART regimens among PLWH is well documented Diiorio et al, 2009;Gordillo, del Amo, Soriano, & González-Lahoz, 1999;Holzemer, 1999;, although few studies have focused on specific roles and mechanisms of social support. A meta-analysis found that, among people with different diseases, practical support was a much stronger predictor of treatment adherence than emotional support , but this analysis excluded studies that involved substance abusing populations.…”
Section: Social Supportmentioning
confidence: 99%
“…financial) support was more closely associated with treatment access (Knowlton et al, 2001). One study found that social support did not directly influence ART adherence among PLWH, but instead acted through the mediators, depression and self-efficacy (Diiorio et al, 2009). Similarly found that social support operated through affect and spirituality in its relationship with efficacy to adhere to ART.…”
Section: Social Supportmentioning
confidence: 99%